The Impact of Strategic Planning on the Reform of Lebanese Public Administration - Charbel El AMMAR (Revista de Management Comparat International)
For Lebanon to reach its future obligations prior to the implementation of “Capital Investment Plan” or what we called “Cedar Project”, the need for strategy in Lebanese Public Administration reform is substantial. An efficient and effective mechanism to deal with change, development, and reform is the application of strategic planning. The aim of this paper is to shed the light on the influence of strategic planning on Lebanese public administration as a major concept for reform and development accompanied with the critical role played by Lebanese government to emphasis on the necessity to apply New Public Management reform culture. Adopting qualitative research method, the paper seeks to offer a wealthy literature about strategic planning and New Public Management and their role in public administration reform. In addition, quantitative research will take into consideration as an empirical study based on a questionnaire to recognize the perception of the Lebanese Ministry of State for Administrative Reform members’ by analyzing five categories; institutional of strategic planning, setting up the strategic basis, strategic planning diagnosis, strategic planning development, and strategic planning implementation. Our findings will illustrate that the process of strategy and strategic planning have been neither documented precisely nor implemented adequately through almost all staffs, committees, and experts in the ministry. The results will contribute to enhance and improve the planning process by implementing a transparent strategic reform process along with New Public Management principles in order for the ministry to reach its future mission, ambitions, and goals.